2016
DOI: 10.4103/0972-2327.194419
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fatigue in Parkinson′s disease: Indian perspective

Abstract: Context:Fatigue is one of the most frequent nonmotor manifestations in Parkinson's disease (PD), having a major effect on quality of life but is not reported in Indian patients.Aims:To evaluate the frequency of fatigue in a cohort of PD population and its correlation with disease.Settings and Design:Fatigue Severity Scale (FSS) was translated and validated in local vernacular language. All patients of PD visiting neurology outpatient department of a tertiary care hospital.Subjects and Methods:A total of 150 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The relation between fatigue and age was reported in 24 studies, two of which found an association between fatigue and higher age. The meta‐analysis for age showed that patients with fatigue were, on average, 1.4 years older than those without fatigue (for the forest plot, see Supplementary Material 5).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The relation between fatigue and age was reported in 24 studies, two of which found an association between fatigue and higher age. The meta‐analysis for age showed that patients with fatigue were, on average, 1.4 years older than those without fatigue (for the forest plot, see Supplementary Material 5).…”
Section: Resultsmentioning
confidence: 92%
“…Male sex was less associated with fatigue in one of 22 cohorts in which this issue was explored. The meta‐analysis did not find an association between fatigue and sex (Supplementary Material 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations